Developing a simulation model for refuse collection for Iloilo City - Portal, Marisol Garcia
The study aims to develop a computer simulation for refuse collection system in urban areas using Iloilo City as the study area. Prime considerations for the simulation are economics and routing schemes. Two interactive models were designed to derive the optimal solution. The models can be subjected to efferent combinations of operating variables and can comparatively be used to determine the cost and quality of operation for each of these combinations. The operating variables examined were crew size, frequency of collection, and truck capacity. A time and motion study was conducted to determine the characteristics and operations of the collection system of Iloilo City. This includes the rate of collection of crews, rate of travel of collection trucks, slack time and unloading time, and the probability distribution of the observed values of these characteristics. The refuse production per street and its daily fluctuations/variations and the characteristics of the street networks of Iloilo city were taken into account.